Development of MSME Economic Empowerment Materials in the New Normal in Matuari District, Bitung - Winda Lombogia; Lihart Lumapow; Cecilia Kewo; Edwin Wantah; Jerry Wuisang (AIBPM Publisher, 2022)
The purpose of this study is to identify the problems faced by Micro, Small and Medium Enterprises (MSMEs) in the new normal and arrange materials for their economic empowerment in the Matuari District, Bitung City. After conducting a content development, the MSME economic empowerment material product was successfully compiled with the Four D development process, with the stages of problem identification and analysis of development needs, prototype design and material, product testing, and product revision. The material developed is the economic empowerment of MSMEs with an outline of characteristics and principles of entrepreneurship, entrepreneurial creativity and innovation, how to get business capital, family financial management, and online marketing. The trial of this MSME economic empowerment material is highly effective.